Adaptation of liver stiffness measurement depth in bariatric surgery candidates with suspected nonalcoholic fatty liver disease. Issue 9 (September 2016) - Ciocan, Dragos; Lebrun, Amandine; Lamouri, Karima; Pourcher, Guillaume; Voican, Cosmin; Njiké-Nakseu, Micheline; Ferretti, Stefano; Courie, Rodi; Tranchart, Hadrien; Balian, Axel; Prévot, Sophie; Perlemuter, Gabriel; et al.
Abstract : Background and aims: A thick layer of subcutaneous adipose tissue may lead to an overestimation of liver stiffness by transient elastography. The aim of this study was to assess whether liver stiffness measurement (LSM) was overestimated using an XL probe in patients with severe obesity and, if so, to reprocess the data to the adapted depth to obtain the appropriate LSM (LSMa). Methods: A total of 152 obese patients prospectively underwent bariatric surgery and needle liver biopsy. Liver stiffness was measured by transient elastography 15 days before. To determine whether the LSM was overestimated, an expert operator retrospectively determined whether the skin-to-capsula distance was greater than 35 mm by analyzing the hyperechogenicity of ultrasound signals and the measured slope between 35 and 75 mm. In the case of an overestimation, a deeper measurement depth was selected to calculate the LSMa. Results: There was an overestimation of the LSM obtained between 35 and 75 mm in 76 patients (50%). Among these patients, the LSMa was obtained between 40 and 75 mm in 49 patients and between 45 and 80 mm in 27 patients. Only the percentage of steatosis was independently and positively correlated with LSM overestimation. The areas under receiver operating characteristic of LSMa was 0.82±0.04 for predicting fibrosis stage F3. The Obuchowski measure was 0.85±0.02. Conclusion: The LSM was overestimated in severely obese patients obtained between 35 and 75 mm using an XL probe in 76 patients (50%), but LSM can be performed correctly in these patients after adapting the measurement depth to deeper beneath the patients' skin.